New Jersey : A History of the Garden State - Veit, Richard F., 1968-; Lurie, Maxine N., 1940- (Book collections on Project MUSE., 2012)
New Jersey: A History of the Garden State is a fresh and comprehensive overview of New Jersey's history from the prehistoric era to the present. The findings of archaeologists, political, social, and economic historians are brought together to offer a new look at the ways in which the Garden State has changed over time. From its pivotal role in the American Revolution to its modern-day suburbs and cities, this book shows how the small state of New Jersey is often a bellwether for the nation.